PENGARUH LATIHAN SIRKUIT (CIRCUIT TRAINING) TERHADAP DAYA TAHAN PADA PEMAIN BULUTANGKIS CLUB PB. BINTANG PUTRA KOTA PEKANBARU - Handrizal '; Ramadi '; Ardiah Juita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrak : The problem in this research is “the influence of training circuit (circuit training) against resistance from the club badminton player PB. Son Star City Pekanbaru?”, so that athletes can perform future and play much better and especially after a certain increase exercise endurance athletes of the previous game to compensate the opponent and maximum future. Forms of this study were (Experiment), with a population of badminton players club PB. Son Star City Pekanbaru. The data in this study is the entire population of 6 people. The tools in this study is the Bleep Test, which is designed to measure the durability. Thereafter, the data are processed statistical normality test using the test at a significant level 0,05α lilifors. The hypothesis is the influence of circuit training (circuit training) opposed. On the basis of the t-test analysis produces Tcount of 6.15 and 2,015 Ttab, Tcount>Ttab means. On the basis of the analysis of statistical data, there are an average of 32.57 Pree-test and the post-test average of 38.9, the data were normally distributed. There is effect of exercise Circuit (Circuit Training) Durability against at Badminton Players Club PB. Son Star City Pekanbaru.Keywords: Training Circuit (Circuit Training), Endurance